A feasibility study of an unsupervised, pre‐operative exercise program for adults with lung cancer. (29th May 2020) - Finley, David J.; Fay, Kayla A.; Batsis, John A.; Stevens, Courtney J.; Sacks, Olivia A.; Darabos, Christian; Cook, Summer B.; Lyons, Kathleen Doyle
Abstract: Objective: The purpose of this study was to explore the feasibility, acceptability and perceived utility of the provision of a wearable fitness device and an exercise prescription from a surgeon, prior to surgery for lung cancer. Methods: A single‐arm, pre–post feasibility study was conducted with 30 participants scheduled for surgery to treat stage I, II or III lung cancer. Participants were given a Garmin Vivoactive HR device and a prescription for 150 min of moderately to vigorous exercise per week. Participants completed assessments on four occasions and completed a semi‐structured interview on two occasions. Descriptive statistics were used to assess the feasibility and acceptability of study procedures, including synchronising the Garmin device and engaging in study assessments. Results: Seventy‐nine per cent of enrolled participants completed the pre‐operative study activities. Seventy‐one per cent of enrolled participants successfully synchronised their device during the pre‐operative period. Data were transmitted from the device to the study team for an average of 70% of the pre‐operative days. Conclusion: This pilot study demonstrated the feasibility and acceptability of a pre‐operative exercise program for patients scheduled to undergo surgery for lung cancer. Trial Registration: The study protocol was registered with ClinicalTrials.gov prior to the initiation of participant recruitment (NCT03162718).